Akademia Lubrańskiego w Poznaniu. Próba wskrzeszenia (1937) - Szczepaniak, Maciej (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
In the period of the Second Republic of Poland two attempts – unfortunately unsuccessful – were undertaken to organize the teaching of theology at university level in Poznań. Endeavors to create a Theological Faculty at Poznań University in the years 1919-1921 did not bring the expected effects. In 1937 Cardinal August Hlond addressed a plea to the Apostolic See to reinstate the Lubrański Academy in Poznań. The Primate’s vision included the construction of a modern building of the academy which he saw as his personal gift to the archdiocese and a “remembrance” of his primateship. The article takes up the above mentioned issue in the light of the Vatican’s archival materials. They allow us to grasp some essential historical facts and provide access to the drafts of the statutes of the intended reactivated Academy. Their publication herein seems to be an interesting contribution to the outlining of a complete history of the Faculty of Theology in Poznań.